LOW INTESTINAL PARASITES AS AN HEALTH INDICATOR IN A MUNICIPALITY OF SOUTHERN BRAZIL WITH INTENSIVE AGRICULTURAL MECHANIZATION - Mortean, Elenita de Cacia Menoci; Moraes Falavignn, Dina Lúcia; Janeiro, Vanderly; Falavigna-Guilherme, Ana Lúcia; Gomes, Mônica Lúcia (SaBios-Revista de Saúde e Biologia, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> In this study was verified the presence of intestinal parasites in children from a municipality with intense agricultural mechanization in the state of Paraná, southern Brazil. The parasitological stool examinations of 5,219 children from zero to 10 years that live in various districts of Campo Mourão were analyzed by the methods of Faust, Lutz and Baermann-Moraes, in 2004 and 2005. At least one parasite species was observed in 19.8% of children. Entamoeba coli (7.2%), Giardia duodenalis (5.2%) and Endolimax nana (2.7%) were the most frequent species. Area with rural characteristics and the peripheries of urban centers showed a higher percentage of parasites compared to central regions. Low intestinal parasites is probably due to mechanization of soil, migration from rural to urban areas, high use of antiparasitic and easy access to public health facilities. <!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> <div style="border-right: medium none; -moz-border-top-colors: none; -moz-border-right-colors: none; -moz-border-bottom-colors: none; -moz-border-left-colors: none; -moz-border-image: none; padding: 1pt 0cm 0cm; border: 2.25pt medium medium solid none none #003366 -moz-use-text-color -moz-use-text-color;"> BAIXO PARASITISMO INTESTINAL COMO INDICADOR DE SAÚDE EM MUNICÍPIO DO SUL DO BRASIL COM INTENSA MECANIZAÇÃO AGRÍCOLA RESUMO Neste estudo foi verificada a presença de parasitos intestinais em crianças de município com intensa mecanização agrícola do Estado do Paraná, Sul do Brasil. Os exames parasitológicos de fezes de 5.219 crianças de zero a 10 anos residentes em diversos bairros de Campo Mourão foram realizados pelos métodos de Faust, Lutz e Baermann-Moraes, em 2004 e 2005. Pelo menos uma espécie de parasito foi observada em 19.8% das crianças. Entamoeba coli (7.2%), Giardia duodenalis (5.2%) e Endolimax nana (2.7%) foram as mais freqüentes. A área com características rurais e de periferia de centros urbanos apresentou maior percentual de parasitoses quando comparado com as regiões mais centrais. O baixo parasitismo intestinal é provavelmente devido à mecanização do solo, a migração da área rural para urbana, o uso elevado de antiparasitário e o fácil acesso aos serviços de saúde pública.